Population density of actinomycetes on flower cultured soils amended with vermicompost - Yáñez-Ocampo, Gustavo; Sánchez-González, María Esther; de la Portilla-López, Nadia; Marmolejo-Santillán, Yolanda; Del Aguila-Juarez, Pedro; Lugo-de la Fuente, Jorge; Vaca-Paulín, Rocío (REVISTA TERRA LATINOAMERICANA, 2020)
The application of agrochemicals to floriculture gradually decreases fertility and populations of benef icial microorganisms of the soil, actinomycetes being biological indicators of edaphic quality. The objective of this study was to compare the changes in population density of actinomycetes in rose, carnation and flower of love floriculture soils, and their treatment with vermicompost. Treatments were flower of love as control, soil with pesticide from rose culture, soil with pesticide from carnation culture, soil with pesticide from rose culture conditioned with vermicompost 40 Mg ha-1 and soil with pesticide from carnation culture conditioned with vermicompost 40 Mg ha-1. During 28 days, total population density of actinomycetes was quantif ied by count plate. The floriculture soils have a sandy-loam texture, and due to their low content of organic matter, vermicompost was added to the treatments. The total actinomycete population of floriculture soils and vermicompost was 1 × 105 CFU g-1 of soil, which indicated a low content. Changes in the population density of actinomycetes were detected in treatments of soils cultured with rose and carnation with and without vermicompost, being higher in soils cultured with rose and carnation without the addition of vermicompost. The changes in the actinomycete population of soils cultured with rose and carnation indicate that these microorganisms are adapted to the application of pesticides. The addition of vermicompost improved the physicochemical properties of the floricultural soils in their respective treatments.